Factors Affecting Employee Engagement of Generation Z during the Transition from COVID-19 Pandemic to Endemic - Erika; Laiman, Benedict; Laurensia, Katarina; Sun, Pannavaro; Djoenarko, Reinaldo Hadisurya (TIJAB (The International Journal of Applied Business), 2023)
Background: Employee engagement is an important factor for companies to consider as it can increase net profit margin by 6% (Kruse, 2015). Based on previous literature, there are thirteen major factors that influence employee engagement, such as: transformational leadership, transactional leadership, corporate social responsibility (CSR), work-life balance, technology, autonomy, respect, growth and development, job significance, having a creative and challenging job, perceived self-worth, performance evaluation and recognition, and organizational bureaucracy. Objective: This research aimed to investigate the factors that influence employee engagement of Generation Z in Indonesia, during the transition from the COVID-19 pandemic to the endemic period. Method: This study collected data through an online survey, which was distributed to service industry employees in Indonesia. The sampling method used was convenience sampling. A total of 94 valid questionnaires were obtained, and all items were graded on a seven-point scale. In addition, 334 people participated in this study. To identify factors that influence employee engagement, exploratory factor analysis was used. Following that, multiple regression analysis was used to investigate the impact of these dimensions on employee engagement. Results: Thirteen factors that influence employee engagement of Generation Z were identified, namely, transformational leadership, transactional leadership, corporate social responsibility (CSR), work-life balance, technology, autonomy, respect, growth and development, job significance, having a creative and challenging job, perceived self-worth, performance evaluation and recognition, and organisational bureaucracy. Regression analysis shows that the factors influencing employee engagement had positive and significant effects on influencing employee engagement of Generation Z, such as: work-life balance, perceived self-worth, transformational leadership, respect and organizational bureaucracy. Conclusion: This study revealed that five main factors were identified as crucial for employee engagement in Generation Z, namely: work-life balance, perceived self-worth, transformational leadership, respect and organisational bureaucracy. Keywords: Employee engagement, Endemic, Generation Z, Pandemic, Workplace